PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. CHANG SHIN INDONESIA KARAWANG - Palahudin Amarullah Taufik; Syifa Pramudita Faddilla (Jurnal Pijar, 2023)
This study aims to determine: (1) the effect of work discipline on employee performance; (2) the effect of work motivation on employee performance; (3) the influence of work discipline and work motivation together on the performance of employees at PT. Chang Shin Indonesia Karawang Closing section. This research is an ex-post facto research with a quantitative approach. The subject of this research consisted of 35 employees of PT. Chang Shin Indonesia Karawang in the closing section. Data collection techniques using questionnaires and documentation. Test the validity of the instrument items using Product Moment correlation and reliability testing using Alpha Cronbach. Analysis prerequisite test consists of normality test, linearity test, and multicollinearity test. Data analysis in order to answer research questions consisted of simple regression analysis and multiple regression analysis